The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18203/2394-6040.ijcmph20161630
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of internet addiction status and effects among medical students

Abstract: Background: The explosive growth of the internet in the last decade has had a huge impact on communication and interpersonal behavior. More and more students are addicted to internet, while spending lots of time surfing on the internet. The present study was conducted considering the above facts, with the objective to assess the level of internet addiction and effects of it among the medical students. Methods: It was a cross sectional study conducted among medical students of PDU Govt. Medical College, Rajkot.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
0
2
1
Order By: Relevance
“…21,1 Similar studies showed that the magnitude of Internet Addiction ranges between 20% to 40% which is less when compared to our study. 1,2,[22][23][24] A study carried out among Engineering students in Tamil Nadu by Deepa Sankar et al showed a magnitude of internet addiction of 35% which is less compared to our study. 25 There is a statistically significant association between professional course and Internet addiction which indicated that medical students were more addicted than the engineering students.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…21,1 Similar studies showed that the magnitude of Internet Addiction ranges between 20% to 40% which is less when compared to our study. 1,2,[22][23][24] A study carried out among Engineering students in Tamil Nadu by Deepa Sankar et al showed a magnitude of internet addiction of 35% which is less compared to our study. 25 There is a statistically significant association between professional course and Internet addiction which indicated that medical students were more addicted than the engineering students.…”
Section: Discussioncontrasting
confidence: 77%
“…19,20 Prevalence rates ranging from 20% to 65% were reported in many studies done in various parts of the world. 2,[6][7][8]11,13,15,19 Possible reasons for this are: (a) students have huge blocks of unstructured time, (b) First time away from parental control without anyone monitoring or censoring what they say or do online, (d) young students experience new problems of adapting to college life and finding new friends, and often end up seeking a companionship by using different applications of the Internet, (e) students desire to escape university sources of stress resulting from their obligations to pass exams, and complete their degrees in the prescribed time with reasonable marks, all of which make Internet overuse a significant cause of concern for parents and faculty. 11 Among the study subjects, 32.7% students reported mild addiction, 24% students reported moderate addiction and 1% reported severe addition.…”
Section: Discussionmentioning
confidence: 99%
“…A total score of 20 indicated no signs of IA, while a total score of 100 represented the most severe IA. We adopted the following criteria, which were used in previous studies: total scores from 20 to 39 were defined as average usage; scores from 40 to 69 were considered to represent frequent problems due to Internet usage; and scores from 70 to 100 were considered to indicate significant problems caused by Internet usage 2628. Using the above-mentioned cutoff scores, IAT was validated by Widyanto and McMurran, and psychometric properties were analyzed 27…”
Section: Methodsmentioning
confidence: 99%